2D Lagrangian Parcel Volume method for drop flux on a cylinder. (September 2016) - Triphahn, Chris; Mickey, Jason; Loth, Eric
Highlights: LPV method allows for zero-diffusion and low number of particles that need tracking. 2-D LPV model was able to accurately predict impact efficiency on a cylinder. Theoretical model developed to predict the impact Reynolds number on a cylinder. Abstract: To predict ice accretion on an aircraft, it is important to computationally track the path and concentration of water particles to the aerodynamic surface. The recently developed Lagrangian Parcel Volume (LPV) method allows for both zero-diffusion and comparatively small amounts of particles to track compared to other numerical methods. The LPV method uses Lagrangian particle trajectories to define a parcel's vertices and enclosed volume. As this parcel volume changes along its trajectory, this allows direct computation of changes in particle concentration. Previous unsteady one-dimensional investigations with the LPV method found that it provides accurate and efficient results when compared with other computational techniques. This study investigated key aspects of the two-dimensional (2-D) LPV method with respect to disperse phase particle concentration and impact efficiency predictions. These aspects included parcel shape definition, sensitivity to number of parcels and trajectory timesteps, as well as integration dynamics with a non-linear drag model and with polydisperse particle distributions. In general, the results indicate the 2-D LPV model as constructed herein was able to accurately predict impact efficiency on an aerodynamically relevant cylinder based on experimental data. In addition, a theoretical model was developed to accurately predict the impact Reynolds number on a cylinder.